Huygens dipole for nanolocalization - Bag, Ankan; Neugebauer, Martin; Wozniak, Paweł; Leuchs, Gerd; Banzer, Peter (Optics InfoBase Conference Papers, 2018)
We discuss a nanolocalization technique with sub-nanometer localization resolution based on position dependent transverse Kerker scattering, obtained via interference of tailored electric and magnetic dipole moments.
CRIS-Team Scopus Importer:2023-04-20